Sosialisas Pemanfaat Aplikasi Canva Guna Pembuatan Desain Merek Dagang di Desa Bedug RT 10/ RW 03 Kecamatan Pangkah Kabupaten Tegal - Itsna Tifani Barokatur Rizqoh (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
The presence of a strong trademark is also a determining factor for the success of a business in today's digital era. An attractive and professional brand design can differentiate the products or services sold from what competitors offer. However, not all business actors, especially enterpreneur activists, have sufficient knowledge and resources to create a quality brand design. Therefore, it is essential to enhance the capabilities of entrepreneurs in consistently producing appealing and effective brand designs. One practical approach is to promote the use of user-friendly graphic design tools, such as Canva, through awareness and outreach programs. With Canva, enterpreneur players can create professional brand designs without the need to have in-depth graphic design skills. The primary aim of this study is to enhance entrepreneurs' skills in designing appealing and professional trademarks by promoting the use of the Canva application through socialization efforts. This research is anticipated to offer the following advantages:: First, increasing the knowledge of enterpreneur about the importance of trademark design. Second, increasing the ability of enterpreneur to use Canva's basic features in creating brand designs. Third, helping enterpreneur in creating brand designs that match the identity of their business profile. This research was conducted in several stages: preparation, implementation, and evaluation. The expected output of this research is an increase in the capacity of enterpreneur stakeholders. After attending the training, the ability of enterpreneur players in Bedug Village, Pangka Sub-district, Tegal Regency to create brand designs increased significantly. New brand designs: new brand designs that are more attractive and professional were created by the trainee enterpreneur. Scientific Publication: The research results can be published in the form of scientific papers or seminar reports to enrich the repertoire of science.